Pengembangan Bahan Ajar Berbasis Kearifan Lokal Silek Penyudon Menggunakan Aplikasi Anflip Di Sekolah Dasar - Amanda Eka Yulistranti; Asrial Asrial; Alirmasnyah Alirmasnyah (Journal on Education, 2023)
The development of technology in the world of education creates a lot of conveniences including increasing learning abilities and facilitating access to learning. But if its use is not balanced with character cultivation, it will cause a decline in values or a crisis of character values. This research was conducted to determine the importance of character education in elementary schools in the digital era. Seeing today's developments, many children use technology for entertainment and lack of social and social character that is not good in society. Therefore, character education is needed to form a quality generation by fostering a sense of responsibility in using technological developments in the digital era. Character education can also make the dimensions of development in children optimally cognitive, physical, social-emotional, creative and spiritual. Character education aims to form and develop people who are obedient to God Almighty, comply with the rule of law, carry out intercultural interactions, apply the noble values of national culture and strengthen the spiritual, moral and ethical foundations as the pride of the Indonesian nation. The method used in this research is qualitative method. The target in this research is elementary school teachers. The data collection technique used in this study was interviews taken from 20 elementary school teachers. The results of the study show that character education in elementary schools is optimal. This can be seen from the results obtained by the researchers in the discussion that from several targets that become references for attitudes or behavior, almost all of them can be achieved by 75%. Success can also be seen from the behavior of students who show the character desired by the teacher according to the targets set. With the numbers obtained and with the attitudes shown by students, it means that character education in elementary schools has achieved optimal success.